METHOD OF IMAGE FACE INVARIATION OF AFFINE DISTORTION - Федоров, Д. М. (Science-based technologies, 2013)
There are analyzed the literature of recognition face images. It is found that the image recognition is not taken into account all the possible types of distortion, in which straight moving in straight lines. Considered in the literature considered only the distortion arising from the displacement in the x-axis or y-axis, proportional increase or reduce (zoom) and rotate it around an arbitrary point chosen in the plane. A considered when faces are detected distortion, which is compressing or stretching the face image, while the image boundaries take the form of a parallelogram. Designed parametric formula for the distorted image so that leads to recognition insensitive to any affine distortion and classification proposed rule, which will be calculated measure of similarity is a representation of the standard.